Anti-Typhoid Activity Test Of Cacao Leaf Fraction (Theobroma Cacao L.) Against Salmonella Typhi Bacteria In Vitro - Dyah Ayu Rara Anggraini; Arif Wijayanto (Strada Journal of Pharmacy, 2024)
Introduction : Cocoa leaves (Theobroma cacao L.) are known to contain compounds with potential antibacterial properties. This study aims to investigate the antibacterial activity of various cocoa leaf fractions against Salmonella typhi. Methods: This experimental study involved the extraction of cocoa leaves followed by fractionation using polar, semi-polar, and non-polar solvents. The antibacterial activity was tested using the agar diffusion method to measure the inhibition zones produced by each fraction against Salmonella typhi. The positive control group used chloramphenicol at a concentration of 400 ppm, while the cocoa leaf fractions were tested at various concentrations. An ethanol-free test was also conducted to ensure no ethanol contamination in the fractions tested. Results: The results showed that the water, ethyl acetate, and n-hexane fractions of cocoa leaves exhibited significant antibacterial activity against Salmonella typhi. The water fraction at a concentration of 600 ppm showed the largest inhibition zone with a diameter of 27.30 mm, which is close to the effectiveness of the positive control chloramphenicol, which had an inhibition zone of 27.70 mm. The ethanol-free test confirmed that no ethanol was detected in the three fractions. Conclusion: Based on the data obtained, cocoa leaf fractions, especially the water fraction, have the potential to be effective natural antibacterial agents against Salmonella typhi. This finding provides a basis for further development in the use of cocoa leaf extracts as an alternative treatment for bacterial infections.